ChemInform Abstract: Iridium‐Catalyzed Reductive Nitro‐Mannich Cyclization. Issue 22 (15th May 2015) - Gregory, Alex W.; Chambers, Alan; Hawkins, Alison; Jakubec, Pavol; Dixon, Darren J.
Abstract: The synthetic utility of this highly diastereoselective cyclization is demonstrated in the synthesis of racemic epi‐epiquinamide (VIII).